Determination of Affecting Factors on Profitability of Banking Sector: An Examination upon the Turkish Banking Sector for the Period of 2006-2018 - Mustafa Tevfik Kartal (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Although net profit of Turkish Banking Sector (TBS) has reached TL 54.1 billion in 2018, the profitability of TBS has been decreasing. Return on assets of TBS has decreased from 2.3% in 2006 to 1.4% in 2018. Similarly, return of equity of TBS has decreased from 18.8% in 2006 to 10.50% in 2018. This figures verify the decreasing trend in profitability. This trend presents risks for limiting of providing credits of banks. Therefore, the level of profitability of TBS has importance. Affecting factors on profitability should be detected first in order to keep profitability stable. In this context, Multivariate Adaptive Regression Splines (MARS) method, 11 explanatory variables, and quarterly data are used between 2006 and 2018. It is determined that net profits, credits, capital, nonperforming loans (NPL)/total credits, total assets, and USD/TL foreign exchange rate (FER) affect the profitability of banking sector in Turkey. Necessary measures should be taken by regulatory authorities to keep net profit stable and increase the profitability of the sector from the current level. Hence, banks could have the opportunity to provide much more credits for financing and supporting economic growth.